Carta de Gilbert K. Harroun a Roberto H. Todd - Todd, Roberto H.; Harroun, Gilbert K. (My University, 1899)
Carta de Gilbert K. Harroun a Roberto H. Todd sobre el Sr. Arturo Schomburg.
Keywords: The Cuban Educational Association; Schomburg, Arturo; Education--Puerto Rico.; Educación--Puerto Rico.